Electronic Devices, Circuits, and Applications - Siu, Christopher; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This textbook for a one-semester course in Electrical Circuits and Devices is written to be concise, understandable, and applicable. Every new concept is illustrated with numerous examples and figures, in order to facilitate learning. The simple and clear style of presentation is complemented by a spiral and modular approach to the topic. This method supports the learning of those who are new to the field, as well as provides in-depth coverage for those who are more experienced. The author discusses electronic devices using a spiral approach, in which key devices such as diodes and transistors are first covered with simple models that beginning students can easily understand. After the reader has grasped the fundamental concepts, the topics are covered again with greater depth in the latter chapters. Focuses on the terminal characteristics of electronic devices, starting from simple models that allow the readers quickly to grasp the idea; Uses a spiral approach to each topic, in which simple models and usage are covered first. After the reader has had practice with using the device, the topic is covered again in subsequent chapter(s) with more details; Includes worked examples of functioning circuits, throughout every chapter, with an emphasis on real applications; Includes numerous exercises at the end of each chapter; Highlights contemporary applications of electronic devices.
Interpreting I-V Curves -- Introduction to the Diode -- Semiconductor Physics -- Introduction to the BJT -- Introduction to MOSFETs -- Single Transistor Amplifiers -- PMOS & CMOS -- Frequency Response -- Device Physics Revisited -- Diode Circuits -- Diode & BJT Equations -- Practical Tips in Electronics -- Index.
Keywords: Electronic circuits; Cooperating objects (Computer systems).; Electronic Circuits and Systems; Electronic Circuits and Systems; Cyber-Physical Systems; Electronic apparatus and appliances; Electronic circuits